2013
DOI: 10.1152/ajplung.00288.2012
|View full text |Cite
|
Sign up to set email alerts
|

Activating the Nrf2-mediated antioxidant response element restores barrier function in the alveolar epithelium of HIV-1 transgenic rats

Abstract: The master transcription factor nuclear factor (erythroid-derived 2)-like 2 (Nrf2) regulates the expression of antioxidant and phase II-metabolizing enzymes by activating the antioxidant response element (ARE) and thereby protects cells and tissues from oxidative stress. Pulmonary complications remain the leading cause of death in human immunodeficiency virus (HIV)-1-infected individuals, who display systemic oxidative stress and glutathione deficiency that can be modeled in transgenic rats where HIV-1-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 45 publications
4
63
0
1
Order By: Relevance
“…This was confirmed by quantitative analysis, where overnight treatment with 5 ng/ml TGF-␤1 resulted in a significant increase in the fraction of cells with spikes containing claudin-18 [16.9 Ϯ 1.5% spike-containing cells (n ϭ 8) vs. untreated controls, 11.7 Ϯ 1.8% spike containing cells (n ϭ 8), P Ͻ 0.05]. A comparable effect on tight junction morphology associated with paracellular leak has previously been observed in AECs isolated from alcohol-fed rats (14) and AEC cells treated with BMS-345541 (55). Note that GM-CSF did not significantly decrease spike formation by AECs either in the absence or presence of TGF-␤1 (10.6 Ϯ 0.9%, n ϭ 8, vs. 14.8 Ϯ 1.3%, n ϭ 8).…”
Section: Differential Effects Of Tgf-␤1 and Gm-csf On Lung Epithelialsupporting
confidence: 53%
See 2 more Smart Citations
“…This was confirmed by quantitative analysis, where overnight treatment with 5 ng/ml TGF-␤1 resulted in a significant increase in the fraction of cells with spikes containing claudin-18 [16.9 Ϯ 1.5% spike-containing cells (n ϭ 8) vs. untreated controls, 11.7 Ϯ 1.8% spike containing cells (n ϭ 8), P Ͻ 0.05]. A comparable effect on tight junction morphology associated with paracellular leak has previously been observed in AECs isolated from alcohol-fed rats (14) and AEC cells treated with BMS-345541 (55). Note that GM-CSF did not significantly decrease spike formation by AECs either in the absence or presence of TGF-␤1 (10.6 Ϯ 0.9%, n ϭ 8, vs. 14.8 Ϯ 1.3%, n ϭ 8).…”
Section: Differential Effects Of Tgf-␤1 and Gm-csf On Lung Epithelialsupporting
confidence: 53%
“…AECs were seeded at 2 ϫ 10 5 cells/well in 12-well 0.4-m Transwell permeable supports (Corning Life Sciences). On day 1, the cells were transfected as described (14) using HiPerFect (Qiagen, Gaithersburg, MD) with 30 nM siRNA duplexes from Sigma-Aldrich that were either specific for rat clau-din-18 (cldn-18 siRNA 1: 5=-GUGAUGAUGUGCAUUGCUU -3=; siRNA 2: 5=-CCAUUUACAGGUUAAGAGA -3=) or control siRNA (Sigma MISSION Universal siRNA negative control; no. SIC001).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…NR2F2 also down-regulates expression of Ang-2, a factor known to decrease junctional protein expression. In a similar way, activation of the nrf-2 pathway by oxidative stress activates antioxidant response elements (ARE), which are known to stabilize ZO-1, occludin, and claudin-5 expression (Fan et al 2013). In addition, nrf-2 protects ECs during injury by supressing the expression of inflammatory genes (Chen et al 2006).…”
Section: Convergence Of Signaling Events At the Bbbmentioning
confidence: 99%
“…The master transcription factor known as nuclear factor (erythroid-derived 2)-like 2 (Nrf2) is known to regulate the expression of antioxidants through activation of antioxidant response element (ARE). Fan et al showed that upregulation of Nrf2 increased the ARE-dependent antioxidants and that HIV-1-related proteins downregulated Nrf2 expression in HIV-1 transgenic rats [29]. Increased oxidative stress induces Nrf2 and stimulates key antioxidant defence mechanism [30] in HIV cells.…”
Section: Induction Of Stress Responses and Stress Response Genes: A Cmentioning
confidence: 99%